Implementación de un sistema audiovisual para el laboratorio de electrónica. - Correa Chalaco, Yofre Pascual (2015)
This Project is focused on the installation of audiovisual media, in order to learn the different knowledge taught in the university, using the appropriate and necessary elements when the knowledge is imparted. Therefore it was decided to install an audiovisual system in the Laboratory of Electronics AEIRNNR, which owns a projector, projection screen, speakers and connections and adequate quality facilities which guarantees efficiency and durability. It also contains drawings, brands, and models of used items. This work is performed under present quality requirements, and ease when running the job for which it is designed.